2022
DOI: 10.1002/hep4.2087
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in hepatocellular carcinoma surveillance among insured patients with hepatitis B infection without cirrhosis in the United States

Abstract: Suboptimal adherence to guidelines for hepatocellular carcinoma (HCC) surveillance among high‐risk patients is a persistent problem with substantial detriment to patient outcomes. While patients cite cost as a barrier to surveillance receipt, the financial burden they experience due to surveillance has not been examined. We conducted a retrospective administrative claims study to assess HCC surveillance use and associated costs in a US cohort of insured patients without cirrhosis but with hepatitis B virus (HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The actual proportion of HCC surveillance among patients with CHB without cirrhosis remains low at about 32%, [38,39] and only about 39% of these patients with CHB without cirrhosis received abdominal imaging after 6 months of follow-up. [40] Another study determined that only a quarter or less of patients with cirrhosis (in general) received HCC surveillance. [41] Several factors may contribute to barriers to effective HCC surveillance in patients with CHB.…”
Section: Barriers To Effective Hcc Surveillancementioning
confidence: 99%
“…The actual proportion of HCC surveillance among patients with CHB without cirrhosis remains low at about 32%, [38,39] and only about 39% of these patients with CHB without cirrhosis received abdominal imaging after 6 months of follow-up. [40] Another study determined that only a quarter or less of patients with cirrhosis (in general) received HCC surveillance. [41] Several factors may contribute to barriers to effective HCC surveillance in patients with CHB.…”
Section: Barriers To Effective Hcc Surveillancementioning
confidence: 99%
“…Multiple barriers persist ( 90 ) at both the provider and patient levels ( 91 , 92 ). For those who have been identified as being at risk for HCC, screening can be inconvenient, and lack of insurance coverage and/or considerable out-of-pocket costs are a concern ( 93 ). The recommended frequency of screening can lead to “surveillance fatigue”; ultrasound requires fasting; and patients report additional challenges, including low awareness about the need for HCC surveillance, transportation challenges, difficulty scheduling, and uncertainty about where to obtain an ultrasound ( 94 , 95 ).…”
Section: Underuse Of Hcc Surveillancementioning
confidence: 99%
“…(2) Our group has demonstrated both patient-and provider-level barriers that will need to be addressed to improve surveillance utilization. (3,4) We believe the more important aspect of our study is the comprehensive review of intervention studies aimed at improving HCC surveillance utilization. We identified eight studies evaluating interventions ranging from patient and provider education to electronic health record reminder systems to population health outreach…”
Section: Replymentioning
confidence: 99%
“…Second, many included studies focused on patients with chronic hepatitis C; however, patients with viral hepatitis are known to have higher rates of HCC surveillance than those with nonviral liver disease. (4) Third, this subanalysis included a large study by Mittal et al (5) that reported a rather high HCC surveillance rate of 46.5%, which is most likely due to this study defining HCC surveillance as having at least one liver imaging test within 2 years before HCC diagnosis instead of regular liver imaging every 6 months. Finally, all included studies in the subanalysis of population-based studies were from countries with high socioeconomic status, and the situation may be even worse in resource-limited areas.Together, the current data suggest that the true rate of HCC surveillance in patients with cirrhosis is probably a great deal less than 10%.…”
mentioning
confidence: 99%